LEGAL ANALYSIS OF THE CONTROVERSY OVER COPYRIGHT ROYALTIES FOR SONGS AND MUSIC IN INDONESIA - Musran, Andi; Muhammad Sabir; Sunardi Purwanda; Bakhtiar Tijjang; Aksah Kasim (RADJA PUBLIKA, 2026)
This study aims to analyze the controversy surrounding song and music copyright royalties in Indonesia and identify the factors contributing to the suboptimal fulfillment of royalty rights for creators. The research method used is normative legal research with an analytical and comparative approach, comparing the royalty management systems in Indonesia with those in the United States. The results indicate that the main problems lie in the lack of transparency of the National Collective Management Institution (LMKN), a weak oversight system, and the suboptimal integrated song and music database. Furthermore, the Indonesian royalty management system still uses a collective approach, which is considered inefficient and does not provide fair legal certainty for creators. Meanwhile, the United States has implemented more transparent and flexible systems, such as direct licensing and technology-based management. This research contributes to providing recommendations for improving the royalty management system in Indonesia to make it more transparent, accountable, and equitable for all parties involved in the music industry.